2019
DOI: 10.1038/s41467-019-09331-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of corneal substrate biomechanics and its effect on epithelial stem cell maintenance and differentiation

Abstract: Whilst demonstrated extensively in vitro, the control of cell behaviour via modulation of substrate compliance in live tissues has not been accomplished to date. Here we propose that stem cells can be regulated solely through in situ modulation of tissue biomechanics. By first establishing, via high-resolution Brillouin spectro-microscopy, that the outer edge (limbus) of live human corneas has a substantially lower bulk modulus compared to their centre, we then demonstrate that this difference is associated wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
134
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(147 citation statements)
references
References 66 publications
(108 reference statements)
13
134
0
Order By: Relevance
“…Brillouin microscopy has previously demonstrated non‐disturbing characterization of cellular mechanics. [ 14–18 ] Although the rigorous relationship between high‐frequency longitudinal modulus, characterized by Brillouin technique, and traditional quasi‐static Young's or shear modulus, obtained with contact‐based techniques is not established in soft biological matter, empirically strong correlations have been observed in many physiological and pathologic processes, suggesting the biomechanical changes occurring within cells alter both moduli in the same direction. [ 17,19,20 ] Here, we validated Brillouin measurements for the characterization of nuclear mechanics and used it to directly quantify the changes of longitudinal modulus of the cellular nucleus in response to both epigenetic regulation and cytoskeletal manipulation.…”
Section: Introductionmentioning
confidence: 99%
“…Brillouin microscopy has previously demonstrated non‐disturbing characterization of cellular mechanics. [ 14–18 ] Although the rigorous relationship between high‐frequency longitudinal modulus, characterized by Brillouin technique, and traditional quasi‐static Young's or shear modulus, obtained with contact‐based techniques is not established in soft biological matter, empirically strong correlations have been observed in many physiological and pathologic processes, suggesting the biomechanical changes occurring within cells alter both moduli in the same direction. [ 17,19,20 ] Here, we validated Brillouin measurements for the characterization of nuclear mechanics and used it to directly quantify the changes of longitudinal modulus of the cellular nucleus in response to both epigenetic regulation and cytoskeletal manipulation.…”
Section: Introductionmentioning
confidence: 99%
“…Targeting ECM mechanics, by preventing or reversing tissue stiffening or interrupting the cellular response, is a therapeutic approach with clinical potential [50]. For example, Gouveia et al [51] showed that substrate stiffness within the native limbal epithelial stem cell (LESC) niche is relevant to SC phenotype and wound healing and that treating the fibrotic, burnt surface of the cornea with collagenase restored the mechanical properties of the tissue and its capacity to support LESCs [51].…”
Section: Discussionmentioning
confidence: 99%
“…1a, b) [1]. The unique paracrine, multicellular and physical properties of the LSC niche signal the LSCs to maintain their stem cell properties [2][3][4]. Reconstructed 3D optical coherence tomography reveals that the limbus architecture comprises a deep and complex network of crypts bordered by the palisades of Vogt (Fig.…”
Section: Introductionmentioning
confidence: 99%